Acts of Complaining as Realized by COVID-19 Survivors in Indonesia: A Gender Perspective - Nur, Nur Lailiyah; Djatmika, Djatmika; Santosa, Riyadi; Sumarlam, Sumarlam (Script Journal: Journal of Linguistics and English Teaching, 2023)
Background: The increase in Covid-19 patients in Kediri City has had a significant influence on a variety of areas, including health services in the hospitals. This paper explicates an overview of how Covid-19 patients complain about health services in hospitals. Methodology: The present study employed qualitative design using sociopragmatics approach. Data was collected from 31 informants of different genders. The data analysis used Trosborg’s theory. Findings: The results show that in Situation 1 (Medical Ward), both female and male patients have similarities in the use of speech act of complaining using annoyance by 37% of female and 36% of male patients, while in Situation 2 (Healthcare Services), there are differences in the use of the complaining strategy across gender. Women tend to use the ill consequences strategy (29%), while men used the annoyance strategy (34%). While the pattern of similarity in the speech act of complaining used across genders shows that the hint strategy (1%) was used by both genders as seen in Situation 2. Conclusion: To sum up, the difference in gender is not always a determining factor or benchmark in determining something including language use, it all depends on the individual's character in responding to something. Women can no longer be considered "super polite" compared to men, because in certain conditions women can be rougher than men, and vice versa. Originality: If the complaints of Covid-19 survivors about health services in hospitals are not revealed, then the public will never know the real conditions in the field. Without intending to diminish the importance of other determining factors and reduce the performance of healthcare workers as a result of their efforts in service, the less optimal service provided by healthcare workers to patients occurs because there is an imbalance between the needs of the survivors and the capacity of healthcare workers to meet those needs.